Penile Ulcer Caused by Lintah Oil Injection - Kartika Paramita; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Lintah oil that was injected for genital augmentation, can cause penile ulcer, which is also one of the ulcer that occur due to ‘self-inflicted’. It could occur in nodul or abscessformation, and undergoes ulceration. It can cause psychological stress to affected patient, so that a proper diagnosis is expected to support well management. Purpose: To describe the clinical manifestation, laboratory examination, and management of penile ulcer caused by lintah oil injection. Case: A 58-year-old male presented a single deep wound on his shaft penis, with diameter ± 2 x 5 cm, undermined, ragged edges, containing pus and easily to bleed, occured about 6 months after the injection of lintah oil, which was used for his genitalia enlargement and performed by untrained person. There were complaints about redness skin and swelling on his shaft penis about 3 months after the injection, which then underwent fester with the sense of burning sensation and painful. Discussion: Blood examination indicated a slightly increase of leukocyte. Pus culture and sensitivity test were performed, while waiting for the result, patient was given cotrimoxazole tablet 480 mg twice daily for seven days. Another examination result were within normal limit. Treatment consisted of oral antibiotic for seven days, and for the wound dressing has given NaCl 0.9% as the wet dressing and covered with framycetin sulfate 1% gauze. Conclusion: Diagnosis of penile ulcer caused by lintah oil injection was established by patient’s history and physical examination. Therapy was given based on culture result. Lesion was healed after 1 month of treatment. Education not to repeat the injection was given to the patient to prevent the recurrence of this condition.